Evaluation on the Implementation of Regional Mapping Referal System in the National Health Insurance Primary Care Services in Boyolali, Central Java - Linda Widyaningrum; Didik Tamtomo; Arief Suryono (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan finance preventive, promotive, curative, rehabilitative services. The referal system is needed to enhance services and to assure patient safety. The purpose of this study is to evaluate the implementation of regional mapping referal system of the national health insurance, at the primary care level.Subjects and Method: This was a qualitative study with fenomenology approach. This study was conducted at Wonosegoro I and Karanggede Community Health Centers, type C Boyolali Pandanarang district hospital, type D Boyolali Simo hospital, and Boyolali District Health Office. Data were collected by in-depth interview, direct observation, and document review.Results: Regional mapping referal system in Boyolali district was implemented under the head of the District Health Office regulation no 440/4214/15 /2014. The number of personal in charge of referal system in Wonosegoro I and Karanggede Community Health Centers, which provided inpatient care was lacking. The infrastructure and equipment were insufficient to address common diseases that consist of 155 diagnoses. The information and communication system has not connected to the referal system facilities. Telephone was used to check about the hospital bed of availability. Therefore, patient information could not be sent to the hospital beforehand.Conclusion: The current infrastructure and equipment at Community Health Centers in Boyolali, Central Java are insufficient to support the regional mapping referal system.Keywords: mapping, referal system, BPJS Kesehatan, primary care.Correspondence: Linda Widyaningrum. School of Medical Records, APIKES Citra Medika, Surakarta, Central Java. Email: linda.ningrum@ymail.comJournal of Health Policy and Management 1(2): 95-101https://doi.org/10.26911/thejhpm.2016.01.02.04